(untitled) (Swiss Medical Weekly, 2019)
AIM OF THE STUDY Although physicians’ home visits are highly valued by patients, and are among the measures that contribute to maintaining elderly patients at home, their number is decreasing worldwide. We aimed to describe the trends in home visits made by general practitioners (GPs) in the canton of Vaud in Switzerland between 2006 and 2015, and to explore their associated characteristics. METHODS We retrospectively analysed billing data from family physicians (internists, generalists and practicing physicians) transmitted to the cantonal trust centre between 2006 and 2015. We explored physician and patient characteristics, first over the entire 10-year study period and then averaged by year. To explore factors associated with the number of home visits, we fitted a mixed effect negative binomial regression of the annual number of home visits per physician. RESULTS Over ten years, 631 physicians billed a total of 451,634 home visits, of which 19.8% (n = 89,966) were emergency visits, and 9.7% (n = 43,915) were over the weekend. Home visits represented 2.5% of all consultations. Although the average annual number of physicians doing home visits remained stable at around 400, the mean annual number of visits per physician decreased from 125 in 2006 to 75 in 2015, resulting in a 40% decline in the absolute number of visits. Male physicians undertook more home visits than their female counterparts did, although the difference diminished over time. Visits to elderly patients (65+) represented 84.2% of the home visits. CONCLUSIONS Although most physicians in the canton of Vaud continue to visit patients at home, the overall number of home visits is declining. Most home visits consist of routine visits to elderly patients. Physicians’ gender, age and specialty are associated with the number of home visits. In the rapidly evolving context of an ageing population and the development of home care, physicians’ role in home care provision should be revised, taking into account patient expectations and current health system constraints.